2012
DOI: 10.1016/j.yjmcc.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XIV is important for growth and structural integrity of the myocardium

Abstract: Collagen XIV is a fibril-associated collagen with an interrupted triple helix (FACIT). Previous studies have shown that this collagen type regulates early stages of fibrillogenesis in connective tissues of high mechanical demand. Mice null for Collagen XIV are viable, however formation of the interstitial collagen network is defective in tendons and skin leading to reduced biomechanical function. The assembly of a tightly regulated collagen network is also required in the heart, not only for structural support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 45 publications
4
47
0
3
Order By: Relevance
“…We found that the TBX5 was bound to promoter regions of key components of the embryonic provisional matrix, including perlecan (HSPG2), 30 fibronectin (FN1), 31,32 fibulin-1 ( FBLN1 ), 33 collagen XIV ( COL14A3 ), 34 versican ( VCAN ), 3537 and versican-degrading protease ADMTS9 . 34 These ECM components play essential roles in cardiac development and are indispensable for normal heart development by regulating heart tube segmentation, chamber specification, endocardial cushion formation, interventricular septal formation, and cardiac myocyte differentiation. 38 Taken together, these data suggest that genes encoding embryonic ECM components are direct TBX5 targets and represent potential novel candidate genes associated with HOS and CHD.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the TBX5 was bound to promoter regions of key components of the embryonic provisional matrix, including perlecan (HSPG2), 30 fibronectin (FN1), 31,32 fibulin-1 ( FBLN1 ), 33 collagen XIV ( COL14A3 ), 34 versican ( VCAN ), 3537 and versican-degrading protease ADMTS9 . 34 These ECM components play essential roles in cardiac development and are indispensable for normal heart development by regulating heart tube segmentation, chamber specification, endocardial cushion formation, interventricular septal formation, and cardiac myocyte differentiation. 38 Taken together, these data suggest that genes encoding embryonic ECM components are direct TBX5 targets and represent potential novel candidate genes associated with HOS and CHD.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a total of 15 module-5 genes have been implicated in the development of HF and HF-related traits. Of these, six genes are predicted to be cardioprotective, as deficiencies promote cardiac remodeling ( Col14a1 [Tao et al, 2012], Dkk3 [Bao et al, 2015], and Timp1 [Ikonomidis et al, 2005]) or decrease angiogenesis and neovascularization ( Olfml3 [Miljkovic-Licina et al, 2012], Srpx2 [Miljkovic-Licina et al, 2009], and Ptn [Li et al, 2007]). In contrast, six genes are probably maladaptive, as their overexpression leads to increases in cardiac remodeling ( Col6a2 [Grossman et al, 2011], Cx3cl1 [Xuan et al, 2011], Egfr [Messaoudi et al, 2012], Pcolce [Kessler-Icekson et al, 2006], and Tnc [Nishioka et al, 2010]), oxidative stress ( Nox4 ), or fibrosis ( Itga11 [Talior-Volodarsky et al, 2012]) during HF.…”
Section: Discussionmentioning
confidence: 99%
“…6. COL15A1 (IVS12 + 1 G>T, Heterozygous) This splicing variant was identified in a 10-year-old boy who presented with mitral valve prolapse and joints hypermobility, and the mouse phenotype appears compatible (Tao et al 2012). Homozygous) This variant was identified in a 12-year-old boy who presented syndromic corneal opacity, mild intellectual disability and an absent corneal reflex.…”
Section: Ces and Novel Disease Gene Discoverymentioning
confidence: 99%